Pengaruh Penggunaan Jenis Pupuk Organik Terhadap Produktivitas Tanaman Semangka (Citrullus sp.): Liusman, Haezah Fatdillah - Liusman, Haezah Fatdillah Liusman, Haezah Fatdillah (Sumber Penyuluhan Pertanian Indonesia, 2023)
The use of inorganic fertilizers on watermelon plants in the long term can affect the soil structure, which will reduce fertility and crop production. Inorganic fertilizers can disrupt the balance and suppress the growth of beneficial microorganisms in the soil. The use of organic fertilizers can improve soil conditions and make them rich in microorganisms, so they will increase the productivity of watermelon plants. The purpose of this study was to determine the effectiveness of various types of organic fertilizers in increasing the productivity of watermelon plants. The method used in this study is a systematic review. The results of the systematic review showed that the use of organic fertilizer concentrations of BIO Urine 50 ml/L water, Aloe Vera POC 4 cc/L water, 50% inorganic Mixed Fertilizer + Rabbit Urine POC 15 ml/L, and Bokashi Fertilizer 112.5 gr/10kg soil can increase plant productivity on leaf length, weight, and diameter of watermelon. The potential of various organic materials such as agricultural and livestock waste can be used as fertilizer, either developed to increase watermelon crop production, maintain soil stability, and suppress farmer input due to the use of inorganic fertilizers.